Stimulation of central α2 receptors attenuates experimental necrotizing pancreatitis - Schneider, Lutz; Jabrailova, Bahar; Salem, Mohamed; Kilk, Karl Michael; Hofer, Stefan; Brenner, Thorsten; Strobel, Oliver; Hackert, Thilo; Werner, Jens (Pancreas, 2016)
Severe necrotizing pancreatitis (SNP) is a disease with relevant morbidity and mortality until today. No specific therapy is in sight. Central α2 agonists such as clonidine and dexmedetomidine are known to have anti-inflammatory effects though the cholinergic anti-inflammatory pathway and are implemented in the clinical routine as adjunct sedative drugs. Their potential effect on SNP has not yet been tested.